The influence of antibiotics on the appearance of magnolia stunting symptoms - Maria Kamińska; Hanna Śliwa (Acta Agrobotanica, 2013)
Treatment of diseased magnolia plants with oxytetracycline, baytril and tylan did not reduce the number of symptomatic plants. However, the sprays with antibiotics promoted the shoot growth, development of symptomless leaves and flower buds. The most efficient were baytril at the concentration of 500 ppm, tylan 200 ppm and oxytetracycline at the concentration of 500 or 1000 ppm. Lower concentrations of baytril and oxytetracycline were not so much effective; higher concentration of tylan decreased the magnolia shoot growth. The effect of antibiotics lasted one season. All the antibiotic treated and control plants, randomly tested by PCR-RFLP, showed the presence of AY(16SrI) phytoplasma and some of them were affected with phytoplasma related with apple proliferation phytoplasma group (16SrX). The obtained results indicated that l). magnolia is a natural host plant of phytoplasmas belonging to aster yellows phytoplasma group and apple proliferation group and 2). they support the suggestion that phytoplasmas are the casual agents of magnolia stunting disease.